Πιθανή εφαρμογή μελατονίνης για τη παρασκευή λειτουργικού γιαουρτιού με βάση το πρόβειο γάλα. - Νικολάου, Μιχαέλλα (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Melatonin is one of the most important hormones for the cause of sleepiness. What is more, the limited quantity of melatonin could cause lack of relaxation and sleepiness. Melatonin’s biosynthesis starts from amino acid tryptophan and after the reactions, the development of melatonin begins. The secretion starts when there is no any light and there is a lot of development during the night unlike daytime where there is no secretion. Also this hormone has beneficial effects on human organism and the last few years it has been used for medical purposes. At the current research the examination of possible application of melatonin has been made for the fabrication of functional yogurt. Three samples of yoghurt produced using sheep’s milk. In the first sample was not added melatonin at all. For the preparation of the second sample, a quantity of 1800 ppm of melatonin was prepared and added into the sample. For the third sample 18000 ppm was used. The effect of melatonin in total lactic acid bacteria contained in yogurt, the effect of melatonin in the organoleptic characteristics of yogurt and finally the durability of melatonin in the 28 days that the product is maintained where studied. ln order to perform the above, microbiological analysis was carried out every three days and the lactic acid bacteria were counted. The result of this research showed that adding melatonin in the samples did not alter the organoleptic characteristics of the product and it had not have any negative effects on the viability of the total lactic acid bacteria. The population of lactic acid bacteria in the three samples remained at the same levels (log10 cfu / g = 4,5-6,5). As regard the keeping of melatonin, there was a gradual decrease in concentration. In the second sample (1800 ppm melatonin), the initial concentration was detected in the sample was 143.9 mg/100g and the final concentration was 48 mg/100g. In the third sample (18000 ppm melatonin), the initial concentration in the sample was 1441.6 mg/100g and the final concentration was 447.8 mg/100g. In milk which has milked in the morning hours, the concentration of melatonin is around 10-40 ng / ml. Therefore, considering the above, we conclude that in yogurt remains a remarkable concentration of melatonin which is beneficial.
Keywords: Melatonin; Sheep milk; Yogurt